2009
DOI: 10.1007/s12529-009-9059-z
|View full text |Cite|
|
Sign up to set email alerts
|

The Construct Validity of the Illness Cognition Questionnaire: The Robustness of the Three-factor Structure Across Patients with Chronic Pain and Chronic Fatigue

Abstract: Method: The ICQ was administered to 821 individuals with chronic pain and 295 patients with chronic fatigue. Confirmatory factor analyses were performed to assess the hypothesized three-factor structure, containing the factors "helplessness", "acceptance" and "perceived benefits". A multi-group analysis was performed to investigate the stability of the factor structure in both groups.Results: Results confirmed the three-factor structure in the two samples. The factor structure was invariant across individuals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
54
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 66 publications
(60 citation statements)
references
References 34 publications
3
54
2
1
Order By: Relevance
“…The total score for acceptance varies between 6 and 24, with higher scores indicating higher levels of acceptance. Psychometric research in samples of Dutch-speaking adults with rheumatoid arthritis, multiple sclerosis, chronic pain and chronic fatigue demonstrated the adequate reliability and validity of the ICQ (Evers et al, 2001;Lauwerier et al, 2010). Reliability of the acceptance scale in the research sample of the present study was good with a Cronbach's α of .82.…”
Section: Questionnairesmentioning
confidence: 47%
“…The total score for acceptance varies between 6 and 24, with higher scores indicating higher levels of acceptance. Psychometric research in samples of Dutch-speaking adults with rheumatoid arthritis, multiple sclerosis, chronic pain and chronic fatigue demonstrated the adequate reliability and validity of the ICQ (Evers et al, 2001;Lauwerier et al, 2010). Reliability of the acceptance scale in the research sample of the present study was good with a Cronbach's α of .82.…”
Section: Questionnairesmentioning
confidence: 47%
“…Factor analysis confirmed that the ICQ-PB items loaded onto a single independent subscale that was reliable in samples with rheumatoid arthritis (α = .84; test-retest reliability = .74), multiple sclerosis (α = .85; test-retest reliability = .68), chronic pain (α = .83), and chronic fatigue (α =.81; Evers et al, 2001;Lauwerier et al, 2010). All six items loaded onto the a priori factor with loadings >.65.…”
Section: Illness Cognition Questionnairementioning
confidence: 79%
“…The ICQ consists of 18 items, measuring three types of illness cognitions, which reflect different ways of dealing with a chronic disease: (1) helplessness (6 items, e.g., "My illness controls my life"), (2) acceptance (6 items: "I can handle the problems related to my illness", "I have learned to live with my illness", "I have learned to accept the limitations imposed by my illness", "I can accept my illness well", "I think I can handle the problems related to my illness, even if the illness gets worse", and "I can cope effectively with my illness"), and (3) perceived benefits (6 items, e.g., "Dealing with my illness has made me a stronger person"). Psychometric research indicates that the ICQ is a reliable and valid instrument in various chronic illness populations including MS [26,44]. In this study, only the Acceptance scale was analyzed, which had high reliability (Cronbach's α = 0.87).…”
Section: Methodsmentioning
confidence: 98%